Diversity and Distribution of Ants (Hymenoptera: Formicidae) Nests in the Anjac Campus, Sivakasi, Tamil Nadu - P Anusuyadevi; SP Sevarkodiyone (Global Journal of Zoology - Peertechz Publications, 2018)
The present communication deals with diversity and nesting habitat of ants in ANJAC, Campus, Sivakasi. In the present investigation, we identified ten species belonging to three subfamilies inside the campus. Richness and evenness were high in dry season while comparing to the wet season. In the study nature of nest, some ant's nests were in the soil, some nests in cracks and concrete, while some nests on trees in this investigation.